1995
DOI: 10.1017/s000748530003306x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plant age, leaf age and virus yellows infection on the population dynamics of Myzus persicae (Homoptera: Aphididae) on sugarbeet in field plots

Abstract: Field experiments in which clip-caged apterae of Myzus persicae (Sulzer) (Homoptera: Aphididae) were monitored on sugarbeet revealed that leaf age, plant age and infection of the host with beet yellows closterovirus (BYV) had very large effects on aphid performance (development, reproduction and survival). On healthy plants performance was much better on young, expanding heart leaves than on older leaves. Performance on senescent leaves was poor. When apterae were kept on young heart leaves all their lives (by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 26 publications
2
26
0
1
Order By: Relevance
“…full pod and beginning seed stages), supporting predictions of the plant vigor hypothesis, and previous studies (e.g. [20], [21], [27], [33], [34]). For example, similar effects of young plant leaves have been demonstrated for Myzus persicae (Sulzer) and Aphis fabae Scopoli (Homoptera: Aphididae), resulting in a bottom-up controlled decline in field populations as the season progressed [20], [21].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…full pod and beginning seed stages), supporting predictions of the plant vigor hypothesis, and previous studies (e.g. [20], [21], [27], [33], [34]). For example, similar effects of young plant leaves have been demonstrated for Myzus persicae (Sulzer) and Aphis fabae Scopoli (Homoptera: Aphididae), resulting in a bottom-up controlled decline in field populations as the season progressed [20], [21].…”
Section: Discussionsupporting
confidence: 89%
“…In previous studies we demonstrated a shift in the within-plant distribution of the soybean aphid, Aphis glycines Matsumura (Hemiptera: Aphididae) towards more mature leaves in response to predation [19]. Population increase of other aphid species on slow-growing plant parts is lower than on vigorous-growing plant parts [20]–[22], as predicted by the plant vigor hypothesis [4], although this is unknown for A. glycines . Therefore, we hypothesize that 1) vigorous-growing plant parts support higher A. glycines population growth rates, and 2) predation on vigorous-growing plant parts results in non-consumptive reductions in A. glycines population growth rates by differentially removing individuals with the highest reproductive potential.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Mi/zus persicae reared on BYV-infected sugarbeet accumulated larger quantities of precipitate which consequently increased their stomach size more than aphids reared on BMYV-infected sugarbeet and healthy sugarbeet. This is somewhat surprising as BYV infection of sugarbeet increases the aphids' growth rate, reproduction rate, nymphal survival and adult weight (Baker, 1960;Akers, 1988;Williams, 1995). However, the precipitate is the precursor to the black deposit which is associated with the premature death of the aphids (Kift & Dewar, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Williams (1995) has shown that the reproductive rate and longevity of Mi/zus persicae (Sulzer) (Hemiptera: Aphididae) decline on mature plants. Kift & Dewar (1996) have linked the early decline in populations of this species on sugarbeet to the occurrence of a black deposit in the aphid's stomach, which may be the cause of early death.…”
Section: Introductionmentioning
confidence: 99%